A Review of the Private Pension System and the Current Situation in Türkiye - Abdüsselam Sağın (Senectus)
This study examines the central role of saving at the individual and societal levels, underscoring its importance for capital accumulation and domestic investment, particularly in developing countries. This study examines the individual benefits of the Private Pension System in terms of providing income security in retirement, smoothing consumption, and increasing the incentive to save through tax benefits. The Private Pension System serves to strengthen long-term saving habits and thus financial discipline among individuals. From a societal perspective, the Private Pension System plays a key role in capital accumulation in Türkiye, promoting the deepening of capital markets and reducing the burden on the social security system. It is also important to note that the PPS provides a crucial safety net for societies with aging populations. Evidence suggests that a reliable source of income has a positive impact on the mental well-being of older people, leading to greater life satisfaction and social participation. PPS contributes to a dignified and satisfying life for the elderly, increasing both financial security and social harmony. With these features, PPS plays an important role in the adaptation of societies to demographic changes and offers sustainable solutions for the future elderly population.